Climate adaptation approaches and key policy characteristics: Cases from South Asia. Issue 78 (December 2017) - Vij, Sumit; Moors, Eddy; Ahmad, Bashir; Md. Arfanuzzaman; Bhadwal, Suruchi; Biesbroek, Robbert; Gioli, Giovanna; Groot, Annemarie; Mallick, Dwijen; Regmi, Bimal; Saeed, Basharat Ahmed; Ishaq, Sultan; et al.
Highlights: Key characteristics for climate adaptation policies are institutional flexibility, adaptive nature, scalability and reflexivity. Four South Asian countries have low contribution in scientific journal articles discussing adaptation policy research. Currently transboundary scale focus is generally missing in adaptation policies. Institutional flexibility and scalability in climate adaptation approaches is vital for shared transboundary resources. Abstract: This paper analyses and assesses how existing policies and approaches in South Asia consider long-term climate change adaptation. Presently, it is unclear what approaches are used in the existing policies to cope with the future climatic changes. Our research framework consists of two components. First, we identify and define key characteristics of adaptation policy approaches based on a review of scientific journal articles. The key characteristics identified are institutional flexibility, adaptive nature, scalability and reflexivity. Second, we analyse the presence of these characteristics in the climate change adaptation policies of Bangladesh, India, Nepal, and Pakistan. Our findings show that the four South Asian countries contribute to only 8% of the total journal articles on adaptation policy, with least papers representing Pakistan and Nepal. Reviewing the adaptation policies, we find that except for the Climate Change Policy of Nepal, none of the policies discusses transboundary scale adaptation approaches. The identified adaptation policies lack focus on shared transboundary resources between the countries, and instead focus at national or sub-national scale. This is reflected by relatively low scores for the scalability characteristic. All the countries show high scores for institutional flexibility, suggesting that changing roles and responsibilities between government agencies for adaptation planning and implementation is accepted in the four countries. We conclude that to prevent a loss of flexibility and to promote scalability of shared transboundary resources, policy approaches such as anticipatory governance, robust decision-making, and adaptation pathways can be useful for long-term climate change adaptation.